Accountability Narratives of Rural School Superintendents and Administrators: Moving from Two- to Three-Level Analysis. Issue 3 (May 2014) - O'Rourke, David; Ylimaki, Rose M.
This article focuses on the broader political sphere as it affects superintendents and other constituents of rural districts. The current landscape of education reform focuses on accountability—particularly at the policy level of both state and federal education agencies. This article draws on the literature and an empirical study that examined how rural superintendents—"held accountable" through reform policy—articulate their experiences. The discussion of cultural and political effects of accountability policy finds insight through local superintendents' norms, beliefs, and commonsensical understandings. Thus far, many of the examinations of No Child Left Behind have analyzed the "inputs–outputs" of accountability reform—whether through critical or empirical inquiry. Furthermore, past examinations primarily focus on either macro- (structural) or micro- (local) perspectives. Findings from this study suggest the need for a third (meso- or regional) level of analysis to understand how leaders articulate accountability experiences.